Between distance and duty: emotional labor in transnational fatherhood among Pakistani migrants in Italy - Haider, Syed Imran (Frontiers in Sociology, 2025)
IntroductionTransnational fatherhood presents unique emotional and caregiving challenges, especially for migrant fathers navigating life across borders. Parenthood studies often focused motherhood in the context of transnational families and men are usually seen from the perspectives of labor laws, immigration policies and economy. This phenomenological study explores the lived experiences of Pakistani migrant fathers in Italy, examining how they balance emotional connections and caregiving responsibilities with economic imperatives being away from their families.MethodsThe study adopted phenomenological approach and 30 in depth interviews were conducted with purposively selected Pakistani migrants residing for at least 5 years in Bergamo and Naples, Italy.Results and discussionThe research highlights six key themes such as (1). Emotional pain of physical separation, (2). Helplessness during family illness/crisis, (3). Emotional impact on special occasions, (4). Fear of weakening family bonds, (5). Guilt, Stress, and Identity conflict, and (6). Coping through faith and hope for relieving emotional sufferings and challenging situations. The results explicate that emotional toll of long-distance fatherhood included feelings of loneliness, guilt and sadness and fathering role was exercised through engaging in digital caregiving and regular communication through audio/video calls using digital technology tools. Extreme feelings of stress and anxiety were reported on the specific occasions including illness or death of a family members and special events like birthdays, marriages or religious festivals. The stories of transnational fathers highlighted their turning to religion and accepting is as fate as vital coping mechanism to relieve emotional strain. The study highlights the need for psychosocial initiatives and engaging activities to reduce the feelings of loneliness.